Design and content validation of a checklist about infection‐prevention performance of intensive care nurses in simulation‐based scenarios - Raurell‐Torredà, Marta; Arrogante, Oscar; Aliberch‐Raurell, Anna María; Sánchez‐Chillón, Francisco Javier; Torralba‐Melero, Martín; Rojo‐Rojo, Andrés; Gomez‐Ibañez, Rebeca; Lamoglia‐Puig, Montserrat; Farrés‐Tarafa, Mariona; Zaragoza‐García, Ignacio (Journal of clinical nursing, 2024)
Objective To design, develop and validate a new tool, called NEUMOBACT, to evaluate critical care nurses' knowledge and skills in ventilator‐associated pneumonia (VAP) and catheter‐related bacteraemia (CRB) prevention through simulation scenarios involving central venous catheter (CVC), endotracheal suctioning (ETS) and mechanically ventilated patient care (PC) stations. Background Simulation‐based training is an excellent way for nurses to learn prevention measures in VAP and CRB. Design Descriptive metric study to develop NEUMOBACT and analyse its content and face validity that followed the COSMIN Study Design checklist for patient‐reported outcome measurement instruments. Methods The first version was developed with the content of training modules in use at the time (NEUMOBACT‐1). Delphi rounds were used to assess item relevance with experts in VAP and CRB prevention measures, resulting in NEUMOBACT‐2. Experts in simulation methods then assessed feasibility, resulting in NEUMOBACT‐3. Finally, a pilot test was conducted among 30 intensive care unit (ICU) nurses to assess the applicability of the evaluation tool in clinical practice. Results Seven national experts in VAP and CRB prevention and seven national simulation experts participated in the analysis to assess the relevance and feasibility of each item, respectively. After two Delphi rounds with infection experts, four Delphi rounds with simulation experts, and pilot testing with 30 ICU nurses, the NEUMOBACT‐FINAL tool consisted of 17, 26 and 21 items, respectively, for CVC, ETS and PC. Conclusion NEUMOBACT‐FINAL is useful and valid for assessing ICU nurses' knowledge and skills in VAP and CRB prevention, acquired through simulation. Relevance for Clinical Practice Our validated and clinically tested tool could facilitate the transfer of ICU nurses' knowledge and skills learning in VAP and CRB prevention to critically ill patients, decreasing infection rates and, therefore, improving patient safety. Patient or Public Contribution Experts participated in the Delphi rounds and nurses in the pilot test.